Self- and Peer-Assessment of Student-Generated Podcasts to Improve Comprehensibility in Undergraduate EFL Students - Albedro Cadena-Aguilar; Claudia Patricia Álvarez-Ayure (Profile: Issues in Teachers' Professional Development)
This study reports on a mixed-methods research project into self- and peer-formative assessment of student-generated podcasts in a group of 18 undergraduate students. The aim was to determine whether there were any gains in the spoken comprehensibility of the participants while having them reflect on and adjust their use of suprasegmentals (thought groups, sentence stress, and intonation). Data were gathered from student logs, student-generated podcasts, and a questionnaire. Results unveiled the exhibition of self-regulated behaviours and gains in comprehensibility. This study highlights the importance of helping learners look critically and reflectively at their own oral production and of incorporating training on suprasegmentals within English as a foreign language courses to help learners communicate more effectively within a globalised context.